2004
DOI: 10.1007/s00167-004-0508-6
|View full text |Cite
|
Sign up to set email alerts
|

Patellar resection during total knee arthroplasty: effect on bone strain and fracture risk

Abstract: Patellae in small knees, or after severe patellar erosion, may be vulnerable to fracture after resection during arthroplasty. The patellar remnant may be thin, while the polyethylene component has a standard thickness. Anterior patellar bone strain was measured in cadaver knees loaded via the quadriceps, from 0 to 90 degrees flexion, with the patella intact, and after resections to 16, 13 and 11 mm thick and replacement by an 8-mm-thick polyethylene component. Strain increased significantly with knee flexion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…In addition, a thin patella resulting from over-resection has had poor strain characteristics, which may contribute to early failure [14,19]. Our primary aim was to investigate whether a reliable relationship could be found between the thickness of the patella and any of its other dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a thin patella resulting from over-resection has had poor strain characteristics, which may contribute to early failure [14,19]. Our primary aim was to investigate whether a reliable relationship could be found between the thickness of the patella and any of its other dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo (Carpenter et al, 2009;Sharma et al, 2012), in vitro (Lie et al, 2005;Matsuda et al, 1997;Merican et al, 2014) and in silico (Amirouche et al, 2013;Fitzpatrick et al, 2011;Takahashi et al, 2012) studies have shown that TKA leads to significant changes in patellar kinematics, forces acting on the patella, and resulting bone strain in comparison with the intact knee. One of the possible causes of these changes can be related to a surgical technique influencing the positioning of the prosthetic components, their rotation around the joint axes, and the amount of bone cut.…”
Section: Introductionmentioning
confidence: 99%
“…Several numerical and in vitro studies showed that reduction of patellar thickness can lead to increase of patellar bone strain (Amirouche et al, 2013;Fitzpatrick et al, 2013;Lie et al, 2005), thus increasing risk of the patellar fracture and possibly contributing to AKP symptoms (Draper et al, 2012;Ho et al, 2014). However, these studies were conducted on cadaveric knees.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have measured strain in the patella, using strain as a measure of risk for patellar fracture and component loosening 9–11. In these experimental cadaveric studies, anterior surface strain was measured using a uniaxial strain gage in specimen sample sizes of between 8 and 20 knees.…”
mentioning
confidence: 99%
“…A strain gage can provide a localized measure of bone strain, but does not fully characterize the strain distribution throughout the volume of bone. For example, Lie et al10 measured a compressive anterior cortex strain in full extension and hypothesized that this would result in a corresponding tensile strain on the posterior resected surface.…”
mentioning
confidence: 99%